SCALAR IMPLICATURE IN FACEBOOK - Lakamau, Feronika (Universitas Negeri Medan, 2023)
This research explores the phenomenon of scalar implicature in Facebook status updates, using Yule's systems theory to dissect the implied meanings conveyed through scalar expressions. The research reveals that scalar implicature significantly influences communication on Facebook, providing more insight into the construction of implicatures. Noteworthy findings include examples of scalar implicature in status updates featuring terms such as